2022
DOI: 10.22598/at/2022.34.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Restaurants: Applying an Extended Technology Acceptance Model

Abstract: SAŽETAK:Model prihvaćanja tehnologije i njegovo proširenje vodeći je teorijski obrazac u istraživanju korisničkog usvajanja pametnih tehnologija općenito pa tako i u ugostiteljstvu i turizmu. U istraživanju je korišten prilagođeni model korisničkog prihvaćanja tehnologije na prihvaćenost novog koncepta digitalne vinske karte i jelovnika u hotelskim restoranima u Hrvatskoj i Srbiji. Rezultati 406 samoispunjujućih upitnika dobiveni su metodom modeliranja strukturnih jednadžbi. Analiza rezultata pokazala je da su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The systemic review presented in this paper on digitalization in the different functional areas of the firm has highlighted that some theories have hardly been taken into account in any of the disciplines considered in this investigation that support aspects of digitalization, DT, and the digital technologies that have been analyzed. The extended technology acceptance model has been employed for the digitalization of the firm in the area of marketing, in order to estimate the degree of consumer acceptance of digitalization (Labus, 2022 ), although adaptive theoretical frameworks centered on the Fishbein-Ajzen behavioral-intentions model have also been used (Fishbein and Ajzen 1975 ; Ajzen and Fishbein 1980 ). Mental process, the motivation of the consumer, attitudinal and behavioral models, and the relations between the consumer and the brand are found among a number of investigations that have significantly increased (Park and Yoo 2020 ).…”
Section: Research Agendamentioning
confidence: 99%
“…The systemic review presented in this paper on digitalization in the different functional areas of the firm has highlighted that some theories have hardly been taken into account in any of the disciplines considered in this investigation that support aspects of digitalization, DT, and the digital technologies that have been analyzed. The extended technology acceptance model has been employed for the digitalization of the firm in the area of marketing, in order to estimate the degree of consumer acceptance of digitalization (Labus, 2022 ), although adaptive theoretical frameworks centered on the Fishbein-Ajzen behavioral-intentions model have also been used (Fishbein and Ajzen 1975 ; Ajzen and Fishbein 1980 ). Mental process, the motivation of the consumer, attitudinal and behavioral models, and the relations between the consumer and the brand are found among a number of investigations that have significantly increased (Park and Yoo 2020 ).…”
Section: Research Agendamentioning
confidence: 99%
“…Digital menus and wine lists have become integral components of the restaurant digitalization process. Digital menus provide more information, greater flexibility in product presentation, more current information, automatic translations into other languages, and various nutritional details (calorie count, salt, fat, saturated fat, sugar, and allergy information) (Labus & Jelovac, 2022). Because a digital interface can more easily incorporate a greater amount of information than a traditional paper format, digital menus can increase customer satisfaction and reduce customer uncertainty during the decision-making process (Beldona et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The research by Goswami et al [ 12 ]. showed that in India only 39% of hotel guests eat in hotel restaurants, 43% of visitors do so in Turkey according to Zorlu et al [ 13 ], while in Croatia the percentage is 45% [ 14 ].Therefore, it is essential to know the eating behavior of tourists so that hotels know what to do to attract guest to their catering services at the hotel. This article aims to show why inhabitants of Poland do not buy full meals at the hotel during holidays.…”
Section: Introductionmentioning
confidence: 99%